Association of Biometric Traits with Growth Hormone Gene Diversity in Raini Cashmere Goats - GOOKI, Fatemeh Gholamhoseinzadeh; MOHAMMADABADI, Mohammadreza; FOZI, Masoud Asadi; SOFLAEI, Mohammad (Walailak Journal of Science and Technology (WJST), 2018)
In recent years, the important effects of growth hormone on a broad variety of physiological parameters, such as lactation, reproduction, growth, and metabolism, have attracted many researchers' attentions. To detect GH gene polymorphism and its association with the biometric traits of Raini Cashmere goats, 300 animals were selected and the animals’ genotype was determined using PCR-RFLP. Two different genotypes (AA and AB) were observed in exons 2 and 3 within the goat GH gene. The genotype frequencies for AA, AB, and BB were 0.15, 0.85, and 0, and frequencies of the A and B alleles were 0.575 and 0.425, respectively. The number of observed alleles, number of effective alleles, expected heterozygosity, observed heterozygosity, mean of heterozygosity, expected homozygosity, observed homozygosity, Nei’s index, Shannon’s index, and Fixation index (Fis) were 2, 1.96, 0.49, 0.85, 0.49, 0.51, 0.15, 0.49, 0.69, and -0.74, respectively. Birth type had a significant effect on the Chest height to earth (T26) trait (P-value = 0.032304). Furthermore, a significant effect of age on some biometric traits were observed in this study. The frequency of the AB genotype for most of the traits were higher in comparison to the AA genotype, although some traits did not show a significant effect, which might be explained by the heterosis phenomenon. According to the results, it can be concluded that allele A of growth hormone is a suitable allele for the THH (Toe height of hand hoof), THF (Toe height of foot hoof), HHF (Heel height of foot hoof), and CHE (Chest height to earth) traits, and allele B is a worthy allele for the NI (Nasal interval), LCI (Lip corner interval), NL (Neck length), CC (Chest circumference), AC (Abdominal circumference), LLF (Leg length of foot), WHC (Wither height to under the chest), and DAD (Dorsal angle distance of scapula to Hänsch point) traits. Therefore, better results in the breeding programs for these traits can be achieved from this information, along with other phenotypic records.